"Maid's Day Off": Leisured Domesticity in the Mid-Twentieth-Century United States. Issue 4 (3rd October 2019) - Heinz, Annelise
Abstract: At the height of the mid-twentieth-century domestic revival, middle-class Jewish women created forms of "leisured domesticity, " marked by temporary female-only recreational spaces in their family-centered arenas. In contrast to other forms of recreation, with mahjong second-generation Jewish women gained an entitlement to peer-oriented leisure in the site of domestic labor: the home. Based on extensive oral histories, Heinz argues that consistent cultural patterns emerged around mahjong. These commonalities created a widespread culture that reached its height in the postwar years of upward mobility, experienced in particularly pronounced ways by Jewish Americans. Although the culture of mahjong could reinforce women's domestic roles as much as undermine them, the weekly mahjong ritual demanded a temporary reallocation of household labor. Understandings of postwar life have largely been shaped by a duality between what defined an idealized domesticity in theory (devoted mothers in family-centered middle-class homes) and the ways that women resisted or were excluded from these norms. In contrast, the practices of leisured domesticity illuminate a multidimensional reality. Mahjong-playing mothers neither overthrew nor fully acquiesced to the powerful norms of postwar American "model" domesticity. Creating a widely accepted rhythm of women's recreation made domesticity more livable by carving out patterns of leisure within it.